RISK PERCEPTION OF CHILI FARMERS IN CONTROLLING ANTHRACHNOSE DISEASE AS A FOCUS OF AGRICULTURAL EXTENSION IN RURAL JAVA - Dyah Woro Untari; Dinda Aulia Reta Adisty; Tyas Niswatun Sa'idah; Arsya Pradhipta Nuryan Siwi; Intan Nur Khasanah; Laura Isti Nugraha Pramudita; Hepy Handayani; Julissa Galarza Villamar; Chaniga Laitae; Subejo Subejo; Najmu Tsaqib Akhda (Universitas Sebelas Maret, 2026)
Environment and economic losses due to anthracnose disease attacks on chilli farming are inevitable, fostering farmers' risk perceptions. Unmanaged risks contribute to inappropriate disease control behaviors that ultimately harm farmers and environment. Risk reduction can be the focus of agricultural extension activities, to reduce losses at the farmer level. This study aims to discover how farmers' risk perceptions influence anthracnose disease control and to formulate relevant extension focuses. The research is conducted in three rural areas in Central Java and the Special Region of Yogyakarta: Purworejo Regency, Wonogiri Regency and Sleman Regency. The mixed-methods approach is carried out through observations on farmers' land and surveys using indicators of Good Horticultural Practices to explore disease control methods, perceptions of pesticide use and farmers' risk perceptions of disease control. The results show that unmanaged farmers' risk perceptions give rise to collective barriers among farmers. The context of locality and farmer institutions is a determinant of farmers’ learning success. Primarily, efforts to reduce risk perception are urgent to be the focus of agricultural extension in rural areas. An extension service that orients farmers to their practices is the key to increasing the confidence of farmers in sustainable disease control.